Impacts and benefits of implementing BIM on bridge and infrastructure projects - Fanning, Blaine, author; Clevenger, Caroline, advisor; Ozbek, Mehmet, advisor; Mahmoud, Hussam, committee member (Colorado State University. Libraries, 2014)
To date, BIM (Building Information Modeling) is not widely utilized in infrastructure asset management. Benefits achieved through implementation in vertical construction, however, suggests that BIM represents significant opportunity for gains in process, material and economic efficiency throughout infrastructure project lifecycles. This research documents the current state of BIM implementation across four (4) regional transportation authorities in the United States. Next it provides a detailed case study analyzing and comparing two current (2013) bridge construction projects, one that uses BIM and one that does not. The results are confirmed by the observed reduction in RFIs and CMOs relative to construction area (SF), cost ($), and average daily traffic, compared to typical construction. Finally, it outlines potential benefits and implications of using BIM for infrastructure asset management by regional transportation authorities and the transportation industry in general. Numerous stakeholders involved with horizontal construction and operation currently seek information regarding the potentially significant benefits of integrating BIM into infrastructure asset management. This research is important because its serves to assess and inform such an imminent transition. The specific contribution of this research is to document and assess the role of BIM implementation on one bridge case study in order to highlight the potential of BIM as a dynamic method to assist throughout the lifecycle of infrastructure assets.
Keywords: BIM; infrastructure